ISIS terrorist organization and its Impact on the National Security of the Arab Maghreb Countries (Algeria is an Example) - Muzahem Mejbel AL-Ghrairi, Arshed; Yousif Mahmood, Raji (International Journal of Psychosocial Rehabilitation, 2020)
Over the course of two decades, the security forces in all their branches were able to gain experience that enabled them to control the course of security reality to some extent. The bitter experience that the Algerian people have experienced with the previous jihadist currents has created a fear for it to repeat the scenario of the black decade that passed through the country. However, at the same time, we must not lose sight of the strength and ability of the organization, despite the blows it receives. The organization has the ability to renew blood in its veins, especially through its sleeping cells, which will be ready to work at any moment they may be instructed to do so.